LABAN / BARTENIEFF SYSTEM AND MOTOR COORDINATION IN CLASSICAL BALLET CLASSES IN THE FORMATION OF DANCE ARTIST-TEACHER - Neila Cristina Baldi (Cena, 2020)
This text discusses a methodological proposal to learnteach classical ballet using the somatic approaches Motor Coordination and the Laban/Bartenieff System. The proposition presented here was developed with undergraduate students in Dance and was part of a doctoral research advocated in 2017. In this way, the text proposes to think how the somatic approaches and principles are present in the formation of the teacherartist of dance.